Trimester-specific reference intervals and profile of coagulation parameters for Chinese pregnant women with diverse demographics and obstetric history: a cross-sectional study - Jing Dai; Peimin Mao; Cunying Pu; Xuefeng Wang; Xiaoyan Liu (BMC, 2023)
Abstract Background Owing to the changes in childbirth policy in China, this work aimed to update the trimester-specific reference intervals (RIs) for Chinese pregnant women with diverse demographics and obstetric history. This study also investigated how advanced maternal age (AMA) (> 35 years old), gravity, and parity influence gestational coagulation parameters. Methods In this prospective cross-sectional study, five coagulation parameters were measured using assays provided by Roche diagnostics on Cobas t 711: prothrombin time (PT), activated partial thromboplastin time (APTT), thrombin time (TT), fibrinogen (Fib), and D-dimer, and the trimester-specific 2.5th -97.5th and 95th (D-dimer only) percentiles RIs were established accordingly. Linear regressions were undertaken to analyze the association with demographic characteristics and obstetric history for each parameter. Results 893 eligible pregnant women in different trimesters and at AMA/non-AMA and 275 non-pregnant healthy women were enrolled. For the first, second, and third trimester, respectively, RIs were as follows: APTT (s): 24.8-35.7, 24.6-34.1, and 23.5-34.7; TT (s): 14.4-17.3, 14.1-16.7, and 14.2-17.5; PT (s): 8.30-10.20, 8.00-9.77, and 7.92-9.57; PT-INR: 0.86-1.06, 0.83-1.02, and 0.82-0.98; Fib (g/L): 2.76-4.97, 3.14-5.31, and 3.44-5.93; D-dimer (µg/ml): 0-0.969, 0-2.14, and 0-3.28. No statistically significant differences were observed in TT, D-dimer, and APTT between the AMA and non-AMA women, while PT and PT-INR were shorter and Fib was higher in the AMA group. The association of gravidity and parity with each coagulation parameter is statistically significant (p < 0.05). PT and PT-INR were shortened and D-dimer decreased as gravidity increased. Longer PT and PT-INR, shorter APPT, higher D-Dimer, and lower Fib were associated with increasing parity. Conclusions This work updated the gestational coagulation profiles of Chinese pregnant women and established trimester-specific RIs accordingly. Establishing specific RIs based on AMA, parity, and gravidity might not be necessary.